Integrasi Religiusitas dalam Pendidikan Karakter: Suatu Pendekatan Holistik - Wandi, Joni Indra; Pebriyenni, Pebriyenni; Sumiarti, Sumiarti; Priyono, Cipto Duwi; Afnita, Nora (Journal of Civic Education, 2024)
Character education is crucial in fostering moral and ethical values, which are essential for shaping responsible, respectful, and civically minded citizens. Effective character education must address not only cognitive and emotional dimensions but also integrate religious values, which are fundamental in guiding personal morals and ethics. This research, conducted at SMPN 1 and SMPN 2 in Kota Pariaman, aims to explore a holistic approach to incorporating religiosity into education. The study employed a literature review and case study analysis to identify strategies and best practices for this integration. Results suggest that embedding religiosity within character education through a well-rounded curriculum, targeted teacher training, and a supportive school environment significantly strengthens students' moral and ethical development. The study concludes that an integrated character education approach, enriched by religious values, can play a pivotal role in cultivating good citizenship. As a result, collaborative efforts from government, educators, and the wider community are essential for the successful implementation of these strategies.